Recent advances on biomedical applications of scaffolds in wound healing and dermal tissue engineering. (19th May 2018) - Rahmani Del Bakhshayesh, Azizeh; Annabi, Nasim; Khalilov, Rovshan; Akbarzadeh, Abolfazl; Samiei, Mohammad; Alizadeh, Effat; Alizadeh-Ghodsi, Mohammadreza; Davaran, Soodabeh; Montaseri, Azadeh
Abstract: The tissue engineering field has developed in response to the shortcomings related to the replacement of the tissues lost to disease or trauma: donor tissue rejection, chronic inflammation and donor tissue shortages. The driving force behind the tissue engineering is to avoid the mentioned issues by creating the biological substitutes capable of replacing the damaged tissue. This is done by combining the scaffolds, cells and signals in order to create the living, physiological, three-dimensional tissues. A wide variety of skin substitutes are used in the treatment of full-thickness injuries. Substitutes made from skin can harbour the latent viruses, and artificial skin grafts can heal with the extensive scarring, failing to regenerate structures such as glands, nerves and hair follicles. New and practical skin scaffold materials remain to be developed. The current article describes the important information about wound healing scaffolds. The scaffold types which were used in these fields were classified according to the accepted guideline of the biological medicine. Moreover, the present article gave the brief overview on the fundamentals of the tissue engineering, biodegradable polymer properties and their application in skin wound healing. Also, the present review discusses the type of the tissue engineered skin substitutes and modern wound dressings which promote the wound healing.